An analysis of the relative importance of healthcare services indicators in South Africa: Utilities Analysis Approach - Gani, Shenaaz (Yayasan Aliansi Cendekiawan Indonesia Thailand (Indonesian Scholars' Alliance), 2024)
Background: There is a wide gap in healthcare access between the poor and the rich in South Africa. The government has implemented several policies to address this gap; nonetheless the complaints about poor healthcare delivery exist. Aims: The objective of this study is to examine the relative importance of healthcare service indicators in Tshwane Municipality, South Africa. Methods: This research uses a utility approach to analyse the relative importance of healthcare service indicators in the context of the Tshwane Municipality in South Africa. The study applies conjoint analysis to better understand healthcare users' preferences for several factors such as service range, waiting time for medications and consultations, waiting time for elective operations, and location. Questionnaire was administered on 280 respondents, comprising the following: Black – 130, Whites – 70, Indians – 40, and Coloured – 40. The data was collected from both public and private healthcare users, and the results were compared using an independent t-test. Results: The study found that there were no statistically significant variations in the mean utilities of public and private healthcare users. The finding suggests that healthcare users' preferences, whether they utilize public or private services, are largely comparable and can be addressed by utilizing unified techniques. The result also demonstrates the most favoured levels for each metric, providing insights into patient preferences and their social impacts. The study further highlights various healthcare preferences of users. Conclusion: This finding emphasises that healthcare users have unique expectations, requiring personalised healthcare delivery. The findings have several recommendations for policymakers and healthcare practitioners to improve service delivery and patient satisfaction. Received: 01 May 2024 | Reviewed: 03 June 2024 | Revised: 12 July 2024 | Accepted: 21 July 2024.